At what spatial scale should risk screenings of translocated freshwater fishes be undertaken - River basin district or climo-geographic designation?. (February 2019) - Dodd, Jennifer A.; Vilizzi, Lorenzo; Bean, Colin W.; Davison, Phil I.; Copp, Gordon H.
Abstract: To inform aquatic conservation policy and management decisions, translocated freshwater fish species, i.e. those native to part but not all of Great Britain (GB), were assessed with the Aquatic Species Invasiveness Screening Kit (AS-ISK) at two spatial levels (River Basin District [RBD] and GB overall), the outcome scores calibrated and analysed to determine the relevance of geographical scale (GB, RBD and freshwater ecoregion) on AS-ISK outcome score rankings. The 16 species assessed received scores that showed limited among-RBD variation, with all but only one species (silver bream Blicca bjoerkna ) receiving the same risk ranking across all RBDs for which they were assessed. A trend of increasing AS-ISK score with decreasing RBD latitudinal location was observed, with two species (bleak Alburnus alburnus and tench Tinca tinca ) found to have significantly higher AS-ISK scores in west-coast RBDs than in RBDs to the north and east, and one species (bleak Alburnus alburnus ) to have significantly higher AS-ISK scores in southern RBDs than in northern RBDs. The Water Framework Directive classification of Scotland was found to be inconsistent with the latitudinal gradients in that country's environmental conditions, which are better reflected in the distinction of northern and southern freshwater ecoregions. The ramifications of these legislative classifications for aquatic conservation are discussed.